Discovery of novel 4-hydroxyquinolines as indoleamine 2, 3-dioxygenase 1 inhibitors by virtual screening - ZHANG Yuping (Di-san junyi daxue xuebao, 2019)
Objective To discover novel indoleamine 2, 3-dioxygenase 1 (IDO1) inhibitors with new scaffold structures by screening ZINC and Chembridge databases using pharmacophore modeling and molecular docking. Methods We performed virtual screening of the ZINC database by molecular docking targeting the enzymatic active site of IDO1. The compounds with high scores were selected for enzyme activity test to find the new leads; A pharmacophore model was constructed based on 3 established IDO1 inhibitors that had been tested in clinical trials for virtual screening of the analogues of the lead compounds. The compounds matching the pharmacophore model were selected for inhibitory activity test, and the molecular dynamics was simulated to explore the binding mode of the compounds to IDO1. Results With molecular docking, we identified 11 lead compounds from more than 2 million virtual compounds and measured their enzyme activity. Among them, ZINC91657208 with a skeleton of 4-hydroxyquinoline was found to effectively inhibit the enzyme activity of IDO1 with an IC50 value of 77.15 μmol/L. Thirty-one analogues were obtained by substructure retrieval with 4-hydroxyquinoline skeleton. Ten compounds were selected by pharmacophore virtual screening and their inhibitory effect on the enzyme activity of IDO1 was tested. Three of the 10 compounds showed obvious inhibitory activities, and among them Chembridge29374490 had the lowest IC50 of 37.78 μmol/L, whose root mean square deviations (RMSD) of the skeleton were 1Å and 2.4Å after equilibrium by molecular dynamics simulation. Conclusion We identified new 4-hydroxyquinoline IDO1 inhibitors from ZINC and Chembridge databases.